(untitled) (Fiep Bulletin - online, 2014)
The 2014 FIFA World Cup is one of the sporting mega events and is configured as an exceptional opportunity for the promotion of sports in the host cities. For this positive legacy to happen it must be previously planned, executed and monitored. This study aimed to present the national structure of the World Cup Cities Project and analyze the results obtained in six host cities of the FIFA World Cup 2014. The results showed that the social and sports legacy was not planned by public managers and there are no systems of control and evaluation of sport in any of the host cities, until the realization of the project World Cup Cities. It is understood that the realization of the project World Cup Cities is already a World Cup impact, by enabling the discussion and reflection on the guarantee of the right to practice sports and to draft a proposal for a policy of sport for the largest municipalities of the country.